2017
DOI: 10.1080/13573322.2015.1077442
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of widening ‘legitimate’ understandings of ability within physical education

Abstract: This article explores the importance of critical discourse in physical education (PE) that focuses on how understandings of ability are defined, practised, and potentially altered. Research continues to indicate that physical educators continue to draw on narrow notions of ability which are influenced by the presence of a pervasive performative culture. Traditional understandings of ability often fail to reflect the wider aims of PE such as developing young people's physical literacy. The theoretical concepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
(95 reference statements)
2
32
0
Order By: Relevance
“…Furthermore, Scraton's (1992), now classic study, showed how girls are marginalised in the field of PE, whereby sport and PE are often seen as incongruent with the female/feminine identity. More recent research has demonstrated that the tendency for young women to disengage with PE continues (Berg & Lahelma, 2010;Croston & Hills, 2017;Fagrell et al, 2012;Mitchell, Inchley, Fleming, & Currie, 2015;Scraton, 2018). These examples illustrate how most gender and PE research is based on the experiences of either females, or males (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Scraton's (1992), now classic study, showed how girls are marginalised in the field of PE, whereby sport and PE are often seen as incongruent with the female/feminine identity. More recent research has demonstrated that the tendency for young women to disengage with PE continues (Berg & Lahelma, 2010;Croston & Hills, 2017;Fagrell et al, 2012;Mitchell, Inchley, Fleming, & Currie, 2015;Scraton, 2018). These examples illustrate how most gender and PE research is based on the experiences of either females, or males (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our aim in investigating what movement capability can mean is an attempt to provide alternative ways of conceiving ability and thereby provide enhanced possibilities to make a difference for students' abilities through education. By doing this we follow up Evans' call for a discussion about the educational aim with the subject PE and an alternative view of ability, which still appears relevant a decade and a half later (Croston and Hills 2017;Quennerstedt 2019). There is, as Evans puts it, a need to be concerned about, discuss, identify and nurture the 'physical' dimension of ability in PE (Evans 2004, 100) if the subject claims to be of educational value.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 97%
“…Additionally, it is difficult to articulate the kind of practical knowledge (Polanyi 1969;Nyberg and Larsson 2014) involved in movement capability. Regardless of reason, we argue that Evans' analysis of physical education's expected educational mission is still relevant in many countries (Croston and Hills 2017;Quennerstedt 2019).…”
Section: Notions Of Ability In Pementioning
confidence: 90%
See 1 more Smart Citation
“…However, research into this topic has faced several difficulties [1] which currently remain. These difficulties lies in the ambiguity of the concept of sport talent [2] and the criteria commonly used for identification [3,4]. Research has been conducted in two directions: top-down and bottom-up.…”
Section: Introductionmentioning
confidence: 99%